Investigation on spectral loss characteristics of subwavelength terahertz fibers - Chen, Hung-Wen; Li, Yu-Tai; Pan, Ci-Ling; Kuo, Jeng-Liang; Lu, Ja-Yu; Chen, Li-Jin; Sun, Chi-Kuang (My University, 2007)
By measuring the spectral loss characteristics of subwavelength-diameter terahertz fibers, our study supports the recent theory proposed by M. Sumetsky [Opt. Lett. 31, 870 (2006)] that diameter-variation-induced radiation is a dominant loss mechanism for subwavelength fibers in the low- (<1%) core-fraction-power regime. This physical mechanism limits the lowest guidable frequency in a subwavelength fiber. (c) 2007 Optical Society of America.